Blast response of a scaled reinforced concrete structure with Two-Leaf cavity infill wall - Toy, Ahmet Tugrul; Onat, Onur; Sevim, Baris (ELSEVIER SCIENCE SA, 2025)
Nuclear power plants, composed of boiler houses, reactors, and other facilities, operate at a high risk of explosion. Engineers design boiler hoses and other facilities to withstand dynamic loads like earthquakes, machine vibrations, wind, and blast loads. However, over time, these structures may cease to meet the requirements of current codes. Therefore, it remains unclear how different materials, their orientations, and their interactions, such as masonry and reinforced concrete, will respond in the event of a blast around a nuclear power plant. Currently, this study aims to evaluate the global and local blast response of single and two-leaf cavity infill wall enclosures with reinforced concrete structures. For this purpose, a scaled structure that is exposed to a shake table experiment has been selected. Then the structural system is numerically modelled by using ANSYSAUTODYN and calibrated based on dynamic identification tests. The explosive amount is fixed at 78 kg to facilitate comparison of two models. For blast analysis of the structural system, two different infill wall typologies and three different scenarios are evaluated. The location of explosives determined the studied cases. We register the analytical blast responses in terms of the pressure, strain, and out-of-plane displacement of the infill wall. We limited the blast analyses to 3 ms. We compared the out-of-plane displacement of single and cavity infill walls with each other and with UFC 3-340-02. According to the findings, the thinner leaf in the Two Leaf Cavity Wall model protects the thicker leaf from damage.
Keywords: Blast response; Infill wall; Two-leaf cavity wall; TNT explosive; Explicit analysis; RC STRUCTURE; MASONRY; MODEL; Nuclear Science & Technology